2006
DOI: 10.1097/01.brs.0000222008.15750.1f
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Height Growth Predominates Over Intervertebral Disc Height Growth in Adolescents With Scoliosis

Abstract: Study Design-A cross sectional study of spinal stereo radiographs of adolescents with scoliosis to measure growth.Objective-To determine the relative contributions of the vertebral bodies and the intervertebral discs to the increase in spinal length between T5 to L5 over the age range 7.5 to 20 years.Summary of Background Data-The progression of spinal deformity (scoliosis) is associated with skeletal growth, but the relative roles of asymmetrical growth and remodelling of the vertebrae and discs during adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 17 publications
1
41
0
Order By: Relevance
“…These differences might contribute to the [17] higher incidence of curve progression in female AIS patients during puberty [1,[3][4][5][6][7][8][9]. Stokes and Windisch [18] found that the spinal growth of patients with scoliosis (between 10 and 20 years of age) occurs almost exclusively by height increases in the vertebrae, not the discs. It could be hypothesized that the more backwardly inclined spine and vertebrae in females with a Risser grade 2-5 might be because of the relatively active anterior vertebral overgrowth that has been documented in female AIS relative to age-and gender-matched controls [22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences might contribute to the [17] higher incidence of curve progression in female AIS patients during puberty [1,[3][4][5][6][7][8][9]. Stokes and Windisch [18] found that the spinal growth of patients with scoliosis (between 10 and 20 years of age) occurs almost exclusively by height increases in the vertebrae, not the discs. It could be hypothesized that the more backwardly inclined spine and vertebrae in females with a Risser grade 2-5 might be because of the relatively active anterior vertebral overgrowth that has been documented in female AIS relative to age-and gender-matched controls [22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Basing on mechanical principles that dorsal shear loads could lead to rotational instability in the mid-and lower thoracic vertebrae [17], Janssen et al [12] suggested that these differences might lead to regional instability and contribute to the increased occurrence of curve progression in female AIS patients. The most significant curve progression of AIS occurred during the pubertal growth period, at which time the vertebral growth plate and spinal processes show accelerated growth [18]; we focused on Fig. 2 The mean sagittal vertebral inclination between males (n = 15) and females (n = 16) with non-fused triradiate cartilage (G1).…”
Section: Discussionmentioning
confidence: 99%
“…In two-dimensional radiographic studies on AIS, contradictory findings have been reported on the individual contribution of the vertebral bodies, as compared to the discs, to the coronal deformity. [66][67][68][69][70][71][72][73][74][75] Because the spinal column in AIS, unlike the normal situation, is longer anteriorly than posteriorly, it has been hypothesized that AIS is the result of active anterior overgrowth of the vertebral bodies, or reduced posterior growth by posterior tethering. 60,61 Furthermore, disorders of bone metabolism have been suggested to play an etiological role.…”
Section: B Segmental 3-d Morphology Of Adolescent Idiopathic Scoliosismentioning
confidence: 99%
“…It was expected that the younger growing animals in the present study would have more metabolically active tissue with a higher rate of tissue synthesis and remodeling and consequently more sensitive to the effects of mechanical stress than in the older (typically 12-weekold) animals reported previously. However, there was little axial direction growth observed in any of the rat discs, similar to the relatively small amount of axial growth of spinal discs relative to growth of the vertebrae previously reported in both adolescent humans [28] and in rats [9].…”
Section: Discussionmentioning
confidence: 84%